PENGARUH PEMBERIAN PUPUK NPK DAN PENGATURAN JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SORGUM (Sorghum bicolor (L.) Moench): hasil, jarak tanam, pertumbuhan, pupuk NPK, tanaman sorgum. - Etika Pitta Septiana; Santosa, Sartono Joko; Triyono, Kharis (innofarm, 2023)
The research entitled "The Effect of NPK Fertilizer and setting planting distance on the Growth and Yield of Sorghum (Sorghum bicolor (L.) Moench)" aims to determine the effect of various doses of NPK fertilizer and setting planting distance on the growth and yield of sorghum (Sorghum bicolor) (L.) Moench). Conducted in November 2022 to February 2023, at the Tohudan TPH Seed Garden located on Jl. Senden, Merten, Tohudan, Colomadu, Karanganyar, Surakarta. Held in November 2022 to February 2023, at the Tohudan TPH Seed Garden located on Jl. Senden, Merten, Tohudan, Colomadu, Karanganyar, Surakarta. The research method used a Complete Randomized Block Design (CRBD) consisting of 2 factors and 3 repetitions. There are 2 research factors, namely NPK fertilizer dose treatment (N) and setting planting distance (J). Data analysis used analysis of variance (ANOVA) and was tested further with the BNJ test at the 5% level. Parameters observed included height of plants, number of leaves, weight of wet stover, weight of dry stover, number of panicles planted, panicle weight of plants, number of seeds per panicle, weight of panicles seeds. The research results show that 1). The dose of NPK fertilizer had an effect on the parameters of height of plants, wet stover, number of panicles planted, panicle weight of plants. The application of NPK fertilizer dose of 300 kg/ha (N2) resulted in the highest plant panicle weight with an average of 151.08 g equivalent to 12.09 tons/ha. 2). The setting planting distance treatment affected the parameters of height of plants observation, wet stover, dry stover, number of panicles planted, panicle weight of plants, number of seeds per panicle, weight of seeds per panicle. Setting planting distance of 50cm x 25cm (J3) resulted in the highest per panicle seed weight with an average of 85.70 g, equivalent to 6.86 tonnes/ha. 3). The interaction of NPK fertilizer doses and setting planting distance did not significantly affect all observed parameters.